(3cJGH GdJhMjOs - (3eLghds
(3ChdgG (B:s
(3cJGH GdJhMjO ; SHMGfc Gddge hHMeOc JhMOJ aj PGJc Yf EOQGcc EfSGf cd YGQa hJaQOJ aj UaGJc abUQ Yf fYJc dSGf cd hGUa JLdjJ aj eLGdj hLhOc aXgQJ aj HOGjY hLhOc (B...s
(3BNQgG (B:s
.. (3hbO cGf EHQGgje fHjG (B.. (3MJi bGd Gddg JYGdi (B{ (3Efj LGYdc ddfGS EeGeG bGd hef PQjJj (B} (3bGd Gddg JYGdi (B{ (3dG jfGd YgOj GdXGdejf (B} (3ef YHO UfeG Gh hKfG dG jchf EeGeG (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eWehSs
Keywords: (3GdJhMjO hGdedd hGdfMds